Perlindungan Hukum Bagi Anak yang Menjadi Korban Kekerasan Seksual - Ardy Trihandhika Kusnanda; Frans Simangunsong (Media Hukum Indonesia (MHI), 2026)
This study highlights how legal standards are used in mass and digital media while examining the legal protection of children's identities as victims of sexual assault. There is a discrepancy between the legislation and actual practices despite a number of rules, including the Sexual Violence Crime legislation and the Child Protection Law. The Pasya case serves as an example of how the victim's name was widely disclosed via digital media, which resulted in re-victimization and detrimental effects on the child's social and academic lives. These results show that without efficient inspection and law enforcement, legislative rules are inadequate. The study comes to the conclusion that in order to adjust to the dynamism of the digital age, the legal protection system must be assessed and reinforced.